Enaction in adaptive architecture - Nils Jager (2016)
Our life is becoming increasingly computerised at nearly all scales, a trend evident in terms such as the Smart City, the Smart Home, or the Internet of Things.The introduction of digital technology enables environments to respond to data gathered from many of our behaviours. A growing eld of architectural design and research focuses on kinetic responses to inhabitant behaviour. However, the speci c modes of interaction as well as the effects of such environ- mental responses on their inhabitants are currently underexplored. Using a literature-based approach, we argue that because such digitally augmented environments respond to bodily behaviours of their inhabitants, one important dimension of investigation is the embodied relationship between the architectural space and its occupant. One perspective that offers insight into this relationship is the so-called enactive approach to cognition, describing mutu- al in uences between inhabitant and environment, which can create autonomous behaviour dynamics. Understanding the enacted relationship between inhabitants and environment will help architects create kinetically responsive environments that bene t their inhabitants physi- ologically and psychologically.The paper concludes with an overview of our lab-based research already conducted and current investigations.